2014
DOI: 10.1016/j.bbrc.2013.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Akt-independent GSK3 inactivation downstream of PI3K signaling regulates mammalian axon regeneration

Abstract: Inactivation of glycogen synthase kinase 3 (GSK3) has been shown to mediate axon growth during development and regeneration. Phosphorylation of GSK3 by the kinase Akt is well known to be the major mechanism by which GSK3 is inactivated. However, whether such regulatory mechanism of GSK3 inactivation is used in neurons to control axon growth has not been directly studied. Here by using GSK3 mutant mice, in which GSK3 is insensitive to Akt-mediated inactivation, we show that sensory axons regenerate normally in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 15 publications
(28 reference statements)
1
40
0
Order By: Relevance
“…Taken together these findings suggest that the appearance of UDP-hexoses peak requires modulation of another pathway besides AKT/mTORC1 and that the level of p-GSK-3 expression does not necessarily affect UDP-hexose content. A recent study has shown that PI3K suppresses the activity of GSK3 by an Akt-independent pathway16 and that inhibition with LY294002 activates GSK3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together these findings suggest that the appearance of UDP-hexoses peak requires modulation of another pathway besides AKT/mTORC1 and that the level of p-GSK-3 expression does not necessarily affect UDP-hexose content. A recent study has shown that PI3K suppresses the activity of GSK3 by an Akt-independent pathway16 and that inhibition with LY294002 activates GSK3.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that GSK can be controlled by PI3K via PKA which physically complexes with GSK15. Recently a further Akt-independent link between PI3K and GSK3 has been identified16.…”
mentioning
confidence: 99%
“…For example, serum- and glucocorticoid-inducible kinase 1 (SGK1) stimulates potassium channel Kv7.1 via Akt-independent PI3K signaling in kidney epithelial cells [29]. Akt-independent inactivation of GSK3, a downstream target of PI3K upon peripheral nerve injury may be required for neuronal regeneration [30]. To regulate the proliferation of melanoma cells, BRAF N600E and PI3K signaling cooperated through Akt-independent effects on protein translation in human melanoma cell lines [31].…”
Section: Discussionmentioning
confidence: 99%
“…It regulates both axon establishment and elongation both during development and in the regeneration of mature neurons through glycogen synthase kinase 3 (GSK3). However, the mechanism of GSK3 control of peripheral axon regeneration is controversial and its function in CNS axon regeneration remains unknown (Jiang et al, 2005; Yoshimura et al, 2006; Kim et al, 2011; Saijilafu et al, 2013; Zhang et al, 2014; Gobrecht et al, 2014). Moreover, Akt links a host of signaling molecules through activation of mTORC1, which regulates cap-dependent protein translation by inhibiting TSC1/2 to allow axon development, growth, and regeneration in CNS (Ma et al, 2008; Li et al, 2008; Morita and Sobue, 2009; Park et al, 2008).…”
Section: Introductionmentioning
confidence: 99%